Ответ:
Пошаговое объяснение:
1.
а) -4,3 + 1,6 = -2,7
в)7
- 9
= -2![\frac{3}{8} \frac{3}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B8%7D)
д) -1,5 - (-0,3) + 1,7 = 0,5
2.
(-5
+ 3
) - (-2,8 - 0,8) = -
+ 3,6 = ![\frac{2}{3} \frac{2}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B3%7D)
3.
а) x - 4.7 = -12
x = -12 + 4.7 = -7.3
б) 1
- y = 2![\frac{3}{8} \frac{3}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B8%7D)
y = 1
- 2
= -2![\frac{11}{12} \frac{11}{12}](https://tex.z-dn.net/?f=%5Cfrac%7B11%7D%7B12%7D)
4.
a) |CD| = 1
- (-5) = 6![\frac{2}{3} \frac{2}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7B3%7D)
б) |MN| = -2.3 - (-4.08) = 1.78
5. 6